PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI, DAN KETERLIBATAN KERJA TERHADAP KINERJA KARYAWAN - Yupiter Gulo (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
The aim of this study is to analyze the influence of transformational leadership, organizational culture, job involvement on employee performance .The data was collected by distributing questionnaires to the respondents in firm. Questionnaires distributed to 70 respondents to fill out the Questionnaires. The findings can be summarized as follows. First, transformational leadership (X1) has no influence on employee performance. Second, the organizational culture (X2) has no influence on employee performance. And third, job involvement (X3), has an influence on employee performance.